FORMATION OF LANGUAGE SUSTAINABILITY OF HIGHER EDUCATION APPLICANTS IN THE UKRAINIAN LANGUAGE CLASSES: PROVING THE NEED - Кулик, Олена Дмитрівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article scientifically substantiates the need to form and enhance the language stability of higher education applicants in the Ukrainian language practical classes. For this purpose, the essence of the «language stability» concept was analyzed. It was found out whether student youth showed it up in daily speech activities. An attempt has been made to confirm / disprove the need to strengthen the applicants for higher education language stability. In order to solve these problems, the following methods were applied: research, analysis, synthesis of linguistic and linguodidactic literature on the research problem (to find out a number of core concepts for scientific exploration), pedagogical observation of applicants’ speech in the educational process, questionnaire survey (to assess the current situation, to confirm / disprove the opinion that the problem of language stability of student youth exists, to convince / make sure that it is necessary to solve it). The research revealed: 1) at the moment there is no generalized, commonly accepted, expressive and clear definition of the concept under study (the author of the article gives her own definition in the context of the problem under discussion); 2) applicants for higher education believe that they speak Ukrainian well, they do not abuse foreign language words, and therefore they show language stability; in nationally biased units, foreign words are used before and Ukrainian matches are left just in case; they do not know alternatives to many of them; borrowings are much more likely to be used than their substitutes; the main reason for such speech behavior is the communicative pressure of society, the language fashion; 3) the problem exists, and therefore there is a need to strengthen the linguistic stability of applicants for higher education. In order to at least partially satisfy this need, the author plans to develop a set of relevant tasks and exercises, which will interest applicants to use matches in their own speech, not only in educational but also in other daily activities